Systematic Review Shows That Work Done by Storm Waves Can Be Misinterpreted as Tsunami-Related Because Commonly Used Hydrodynamic Equations Are Flawed - Cox, Rónadh; Ardhuin, Fabrice; Dias, Frédéric; Autret, Ronan; Beisiegel, Nicole; Earlie, Claire S.; Herterich, James G.; Kennedy, Andrew; Paris, Raphaël; Raby, Alison; Schmitt, Pál; Weiss, Robert (Frontiers in Marine Science, 2020)
Coastal boulder deposits (CBD), transported by waves at elevations above sea level and substantial distances inland, are markers for marine incursions. But whether they are tsunami or storm deposits can be difficult to determine. Equations from seminal work by Nott (1997), here referred to as the Nott Approach, are commonly employed to calculate nominal wave heights from boulder masses, as a means to discriminate between emplacement mechanisms. Systematic review shows that this approach is based on assumptions that are not securely founded, and that direct relationships cannot be established between boulder measurements and wave heights. A test, using an unprecedented dataset of boulders moved by storm waves (which associated sea-state data), shows the lack of agreement between Nott Approach calculations and actual wave heights. The equations return unrealistically large heights, many of which greatly exceed sea states occurring during the boulder-moving storms. This underscores the finding that Nott-Approach wave-height calculations are unreliable. The result is general, because although the field data come from one region (the Aran Islands, Ireland); they represent a wide range of boulder masses and topographic settings, and present a valid test Nott-Approach equations. This systematic review and test case demonstrates that Nott Approach equations are incapable of distinguishing storm wave from tsunami transport, and that wave heights hindcast from boulder masses by this mechanism are not meaningful. The current state of hydrodynamic understanding does not permit reliable computation or hindcasting of wave height from the characteristics of coastal boulders; therefore it is not possible to replace the Nott Approach with alternative equations. A combination of field, numerical, and experimental approaches are required to quantify relationships between wave power and boulder transport. Many CBD interpreted as tsunami deposits based on Nott-Approach analysis may in fact have been emplaced during storms, and should therefore be re-evaluated. This is especially important for CBD that have been incorporated into long-term coastal risk assessments, which are compromised if the CBD are misinterpreted. CBD dynamics can be better determined from a combination of detailed field measurements, modelling, and experiments. Clearer understanding of emplacement mechanisms will result in more reliable hazard analysis.